Testing the Usability of Communication Materials through Heat Maps in Online Survey Platforms - Laura M. Gorham; Shuyang Qu; Ricky Telg; Alexa J. Lamm (Journal of Applied Communications, 2016)
Usability tests can be used to enhance the communication strategies of agricultural organizations as they identify the use and value of a communications tool from a target audience’s perspective. Further, online survey methodology has provided a place where communicators can gather information from a diverse target audience. One way communicators can create a usability test in online surveys is through the use of heat map questions. Heat map questions provide a platform where agricultural communication professionals and researchers can identify how well a target audience uses a communication material. By merging heat maps and value-based questions, researchers and communicators can evaluate the usability and value of a communication material. Heat maps allow agricultural communicators to evaluate communication materials such as websites and iers, gather users’ feedback and identify strategies to enhance agricultural communication materials. This article provides steps to incorporate heat map questions into online survey, tips for using heat map tests, and methods to interpret heat map results.
Keywords: Heat Map; Survey Methods; Usability Testing; Value Testing